Dehydration of celery by infrared drying - Ježek, Damir (Array, 2008)
Summary: In this work kinetics of dehydration process was investigated according to dehydration temperature changes, samples dimensions and technological treatment of samples. Investigations were conducted at two working temperatures: 50 °C and 75 °C. Samples were cut into 5x5x5 mm cubes and 20x5x1 mm gratings. Tests were carried out on fresh and blanched samples. Celery samples dehydration was performed in a laboratory infrared dryer (DIR) Mettler LJ16 (Mettler, Switzerland). Sample mass changes were followed during dehydration. For all process conditions (dehydration temperature, sample dimensions and technological treatment), the mass content of dry matter in samples, moisture content, diffusion coefficient and dehydration rate were determined. Diffusion coefficient was the highest for celery gratings at temperature of 75 °C – 2.38x10–6 m2 min–1, and the lowest for celery cubes at temperature of 50 °C – 1.4x10–6 m2 min–1